Moderating Islam Through Indonesian Muslim Manuscript on Ngariksa YouTube Channel: The Study of Sufi's Understanding on the Qur'an and Hadith Text - Muhammad Rikza Muqtada (UIN Sunan Kalijaga Yogyakarta, 2021)
Manuscripts that teach a moderate religious understanding are considered capable of warding off ideological conflicts and maintaining security and stability. This paper shows how the strategy of Muslim philologists to moderate religious understanding, especially in the Qur'an and hadith understanding, through the introduction of ancient manuscripts packaged in the online study of the Ngariksa YouTube channel. Using the digital humanities approach of David M. Berry, Ngariksa’s activity is a part of the socio-cultural practice as a system of knowledge that is carried out in a plural manner, in the sense that information, materials, archives, and documents that are digitally documented can influence the institutionalization of science mediated by new technology, such as computing and internet. In the socio-cultural practice in the digital space, it is necessary to change the character of the Indonesian Muslim community in a more moderate. This change is due to the classical narratives containing moderate past knowledge from moderate figures. In this context, Ngariksa presents Ibrahim al-Kurani's perspective on Sufism that is based on the outer and inner meanings of the texts of the Qur'an and Hadith. An understanding based on just outward meaning is vulnerable to religious extremism.